Interreligious Literacy Learning as a Counter-Radicalization Method: A New Trend among Institutions of Islamic Higher Education in Indonesia. Issue 4 (2nd October 2021) - Ali, Nur; Afwadzi, Benny; Abdullah, Irwan; Mukmin, Muhammad Islahul
ABSTRACT: Extremism and radicalization have become serious problems that are spreading rapidly around the world, penetrating even institutions of higher education in Indonesia. In response, institutions of Islamic higher education in Indonesia have developed interreligious literacy (IL) learning. To analyse this model's effectiveness in reducing radicalization, this article maps recent changes in the management of religious lectures and courses by focusing on two renowned institutions in Indonesia: Maulana Malik Ibrahim State Islamic University (UIN), Malang, and Tulungagung State Islamic Institute (IAIN). This study finds that IL learning involves direct learning at Christian colleges and places of worship, living in villages, and inviting leaders of various faiths to institutions of Islamic higher education. Under this model, religious learning has shifted from a doctrinal to a humanistic-functional approach. This article presents the IL model as a 'best practice' and urges the revitalization of religious education materials and learning models to improve students' religious experiences and communicate peaceful, inclusive and humanistic religious values.